Hubungan Self Esteem Dengan Kecenderungan Narsistik Pada Pengguna Media Sosial di SMA Negeri 51 Jakarta - Elsa Novita Rahayu (Observasi : Jurnal Publikasi Ilmu Psikologi, 2024)
This research aims to determine the relationship between self-esteem and narcissistic tendencies in social media users at SMA Negeri 51. Self-esteem is a person's attitude based on perceptions of how he appreciates and assesses himself as a whole, in the form of a positive or negative attitude towards himself. Narcissistic behavior is behavior that strengthens and increases self-admiration which can provide social status, praise and attraction. The relationship between these two things will be found out. The explanation of the research methods in this research includes Identification of Research Variables. The results of this research show that there is a relationship between the level of self-esteem and the tendency towards narcissistic behavior among social media users at SMA Negeri 51 Jakarta.